Pollination and dispersal trait spectra recover faster than the growth form spectrum during spontaneous succession in sandy old‐fields. Issue 3 (24th April 2019) - Fantinato, Edy; Sonkoly, Judit; Silan, Giulia; Valkó, Orsolya; Tóthmérész, Béla; Deák, Balázs; Kelemen, András; Miglécz, Tamás; Del Vecchio, Silvia; Bettiol, Francesca; Buffa, Gabriella; Török, Péter
Abstract: Question: Spontaneous succession is the most natural and cost‐effective solution for grassland restoration. However, little is known about the time required for the recovery of grassland functionality, i.e., for the recovery of reproductive and vegetative processes typical of pristine grasslands. Since these processes operate at different scales, we addressed the question: do reproductive and vegetative processes require different recovery times during spontaneous succession? Location: Kiskunság sand region (Central Hungary). Methods: As combinations of plant traits can be used to highlight general patterns in ecological processes, we compared reproductive (pollination‐ and dispersal‐related) and vegetative (growth form) traits between recovered grasslands of different age (<10 years old; 10–20 years old; 20–40 years old) and pristine grasslands. Results: During spontaneous succession, the reproductive trait spectra became similar to those of pristine grasslands earlier than the vegetative ones. In arable land abandoned for 10 years, pollination‐ and dispersal‐related trait spectra did not show significant difference to those of pristine grasslands; anemophily and anemochory were the prevailing strategies. Contrarily, significant differences in the growth form spectrum could be observed even after 40 years of abandonment; in recovered grasslands erect leafy species prevailed, while the fraction of dwarf shrubs and tussock‐forming species was significantly lower than in pristine grasslands. Conclusions: The recovery of the ecological processes of pristine grasslands might require different amounts of time, depending on the spatial scale at which they operate. The reproductive trait spectra recovered earlier than the vegetative one, since reproductive attributes first determine plant species sorting at the regional level towards their respective habitats. The recovery of the vegetative trait spectrum needs more time as vegetative‐based interactions operate on a smaller spatial scale. Thus, vegetative traits might be more effective in the long‐term assessment of restoration success than the reproductive ones. Abstract : During grassland recovery by spontaneous succession, reproductive trait spectra typical of pristine grasslands recover earlier than the vegetative one. Reproductive and vegetative traits are involved in processes that sort species into local communities by operating at different scales. Reproductive traits determine plant species sorting at the regional level, while vegetative traits are involved at smaller spatial scales.